2005
DOI: 10.1111/j.1523-1755.2005.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin expression in acute renal allograft rejection

Abstract: These data suggest that inducible expression of OPN in the tubular epithelium may have a pathogenic role in acute renal allograft rejection by mediating interstitial monocyte infiltration and possibly tubular regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…*P < 0.05 and **P < 0.01. ,Mki67,Fga,Fgg,Krt8,Krt18, and Krt19, were selected as candidate biomarkers because (i) there was the strong evidence supporting their usefulness as nephrotoxicity biomarkers in rats and other species (Alchi et al, 2005., Davis et al, 2004Dieterich et al, 2009;Kharasch et al, 2006;Thukral et al, 2005;Wang et al, 2008) and (ii) these selected genes were considered to be biologically related to the gene categories, such as tissue remodeling, inflammatory responses, and cell growth. The usefulness of these genes as nephrotoxicity biomarkers in mice was evaluated further through expression profiling under several experimental conditions using real time RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…*P < 0.05 and **P < 0.01. ,Mki67,Fga,Fgg,Krt8,Krt18, and Krt19, were selected as candidate biomarkers because (i) there was the strong evidence supporting their usefulness as nephrotoxicity biomarkers in rats and other species (Alchi et al, 2005., Davis et al, 2004Dieterich et al, 2009;Kharasch et al, 2006;Thukral et al, 2005;Wang et al, 2008) and (ii) these selected genes were considered to be biologically related to the gene categories, such as tissue remodeling, inflammatory responses, and cell growth. The usefulness of these genes as nephrotoxicity biomarkers in mice was evaluated further through expression profiling under several experimental conditions using real time RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…5 Gene profiling experiments performed on acute and chronic glomerulonephritis 6,7 and transplant renal disease 8 also found Opn mRNA to be highly increased and that it was one of the top genes that predicted renal damage. 5,9 Similarly, gene array studies performed on isolated podocytes identified Opn as the gene with the highest increase in mRNA expression after sheer stress 10 ; however, the reports are conflicting as to whether Opn plays a role in murine autoimmune glomerulonephritis.…”
mentioning
confidence: 99%
“…28,30 Occupancy of ␣ v ␤ 3 integrins can decrease monocyte binding capacity to ICAM-1 and VCAM-1, which are up-regulated in acute allograft rejection. 21,49,51,54 We and others 17,32 have shown that tubular osteopontin expression is significantly enhanced in renal biopsies with acute rejection and could be correlated with interstitial macrophage infiltration and cell proliferation. Osteopontin is an extracellular matrix protein containing an RGD sequence, which can interact with at least three different ␣ v -containing integrins, ␣ v ␤ 1 , ␣ v ␤ 3 , and ␣ v ␤ 5 ; its migratory activity seems to depend on the presence of a functional ␣ v ␤ 3 on the cell surface.…”
Section: Discussionmentioning
confidence: 94%
“…15,16 Furthermore, ligands of ␣ v ␤ 3 integrin include osteopontin, fibronectin, fibrinogen, thrombospondin, von Willebrand factor, collagen, and matrix metalloproteinase (MMP)-2, which are also present in rejecting transplanted organs. [17][18][19] The recruitment of leukocytes from the blood into tissue is essential for the development and maintenance of inflammation in acute rejection and is regulated by a complex network of cytokines, chemokines, and adhesion molecules. 12,20 ␣ v ␤ 3 was found to promote monocyte migration, to be involved in neutrophil mobility on extracellular matrix substrates in vitro, and leukocyte migration across the mesenteric endothelium in vivo.…”
mentioning
confidence: 99%